IPSAS adoption, technological innovations and good governance: Catalysts for public sector sustainability - Nzama, Lethiwe; Ogundele, Omobolade Stephen (Edelweiss Applied Science and Technology, 2025)
The study investigates the interrelated roles of technological innovations, the adoption of International Public Sector Accounting Standards (IPSAS), and good governance as catalysts for sustainability in the public sector. A systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach was conducted on peer-reviewed publications from 2010. The year 2010 was chosen as the baseline due to the increasing prominence of IPSAS implementation across African countries. Data sources include Google Scholar, Elsevier, and Web of Science databases. The study revealed that technological innovation, IPSAS adoption, and good governance structures are mutually reinforcing elements that significantly contribute to the sustainability of the public sector. However, challenges such as limited digital capacity, weak institutional frameworks, and inconsistent enforcement of policies hinder progress in many developing countries. The study concludes that the adoption of IPSAS, innovative technology, and robust governance mechanisms are essential for sustainable public financial management and improved transparency in the public sector. It recommends developing a holistic governance framework aligned with IPSAS implementation and technological development to enhance accountability, efficiency, and long-term sustainability in the public sector.